2008
DOI: 10.1111/j.1600-0897.2007.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Lack of Consistent Association Between Endothelial Nitric Oxide Synthase Gene Polymorphisms, Homocysteine Levels and Recurrent Pregnancy Loss in Tunisian Women

Abstract: The present study identified a lack of association between eNOS gene polymorphisms, the risk of RPL and tHcy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Previous studies have demonstrated a lack of consistent association between the rs2070744 polymorphism and recurrent pregnancy loss in Tunisians (Zammiti et al, 2008) and Koreans (Shin et al, 2010). The current study suggests that this polymorphism was unassociated with the development of RSA in a Chinese population sample.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have demonstrated a lack of consistent association between the rs2070744 polymorphism and recurrent pregnancy loss in Tunisians (Zammiti et al, 2008) and Koreans (Shin et al, 2010). The current study suggests that this polymorphism was unassociated with the development of RSA in a Chinese population sample.…”
Section: Discussionmentioning
confidence: 56%
“…It has been shown that nitric oxide release by endothelial cells is reduced by high Hcy levels. Reduction in nitric oxide leads to platelet adhesion and aggregation, thus promoting thrombosis and vascular diseases (Erol et al, 2007); this may affect blood supply to the placenta and the fetus (Zammiti et al, 2008). In addition to the vascular endothelial cells, Hcy can also affect the structure and function of blood vessels by regulating smooth muscle cell proliferation (Zou et al, 2010) and migration (Jiang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The association between eNOS gene polymorphisms and recurrent early pregnancy losses has been studied among various ethnic groups, including Caucasian, South Indian, Chinese, Greek, and Tunisian (Tempfer et al, 2001;Suryanarayana et al, 2006;Fan et al, 2007;Karvela et al, 2008;Zammiti et al, 2008). The results of the various studies conflicted with each other.…”
Section: Discussionmentioning
confidence: 92%